1985
DOI: 10.1002/etc.5620040513
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxicity of tebuthiuron to an alga (Selenastrum capricornutum), a cladoceran (Daphnia magna), and the fathead minnow (Pimephales promelas)

Abstract: Chronic toxicity studies were conducted with an alga (Selenastrum capricornutum), a cladoceran (Daphnia magna) and the fathead minnow (Pimephales promelas) to determine their relative sensitivities to tebuthiuron, a soil‐applied herbicide. The alga was the most sensitive of the three species. The no observed effect concentrations for the studies with the fathead minnow (9.3 mg/L) and the cladoceran (21.8 mg/L) were higher than the algistatic concentration (1.5 mg/L) for Selenastrum. These concentrations are 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Several researchers (Daniels and Allan, 1981;Ingersoll and Winner, 1982) have suggested that survival in chronic toxicity tests is the best index of toxicity because it is more sensitive and less variable than reproductive parameters. Day and Kaushik (1987), however, suggested that survival is only a good indicator when exposure to (Meyerhoff et al, 1985). * Significantly different from control (P < 0.05).…”
Section: Cladoceran Life-cycle Studymentioning
confidence: 87%
See 1 more Smart Citation
“…Several researchers (Daniels and Allan, 1981;Ingersoll and Winner, 1982) have suggested that survival in chronic toxicity tests is the best index of toxicity because it is more sensitive and less variable than reproductive parameters. Day and Kaushik (1987), however, suggested that survival is only a good indicator when exposure to (Meyerhoff et al, 1985). * Significantly different from control (P < 0.05).…”
Section: Cladoceran Life-cycle Studymentioning
confidence: 87%
“…Approximately 5 × 10 5 cells/ml of N. oculata were added daily to each beaker to feed the daphnids . The young cladocerans used in this test were the second or a successive brood from stock animals (Meyerhoff et al, 1985).…”
Section: Algal Assaymentioning
confidence: 99%
“…For simazine, 48 h-LC50s for D. magna were scored at 1 and 3.5 mg L -1 by Sanders (1970) and Marchini et al (1988), respectively. For tebuthiuron, D. magna toxicity was estimated to be 100 mg L -1 (Meyerhoff et al, 1985). Interactions between free chlorine, THMs and/or herbicides found in FW and TW in October 2010 cannot, however, be excluded as a possible explanation for at least some of the observed toxicity toward daphnids.…”
Section: Whenmentioning
confidence: 95%
“…Martin et al (2003) (Chu et al, 2005). Meyerhoff et al (1985) observed a lower length in D. magna exposed to the herbicide tebuthiuron than in blank control animals when the cladocerans were exposed to 44.2 mg/L herbicide. Hanazato (1998) indicated that the neonatal body size determines the size at maturation.…”
Section: Amino Acid Synthesis Inhibitorsmentioning
confidence: 72%